O consumo crônico de aguardente de cana-de-açúcar induz efeitos ansiolíticos em camundongos - Sena, Maria Clécia Penha (2012)
Distilled sugarcane spirit is a genuine Brazilian beverage produced by distillation after fermentation of sugarcane and is appreciated not only in Brazil but worldwide. Although sugarcane spirit consumption is an important drive to increase alcoholism in Brazil, little is known about its chronic consumption on anxiety/anxiolytic effects. In the present study, we investigated whether the chronic consumption of sugarcane spirit is responsible for inducing anxiolytic-like effects. Male 3-3.5 month-old Swiss mice were exposed to the two-bottle free-choice paradigm for six weeks. Mice in group A were treated with sugarcane spirit + distilled water (n=16); in group B with ethanol + distilled water (n=15); and in group C (control) with distilled water + distilled water (n=14). The content of ethanol in beverages offered to groups A and B was 2% in the first week, 5% in the second week and 10% in the 4 remaining weeks. At the end of the treatments, animals were submitted to the elevated plus maze and the hole board test for assessment of anxiety-related behaviors. Serum aspartate aminotransferase (AST) and alanine amino transferase (ALT) levels were determined. The concentrations of ethanol, volatile acidity, esters, aldehydes, furfural, higher alcohols (n-propylic, isobutylic and isoamylics), methanol, copper and lead of the sugar cane were also determined. Time spent in open arms was increased in mice exposed to chronic ethanol (32±8 vs 7±2 s, p<0.05) or sugarcane spirit (36±9 vs 7±2 s, p<0.05), when compared to the control group. Conversely, the time spent in the closed arms was significantly decreased in animals drinking ethanol (183±6 vs 214±4 s, p<0.05) or sugarcane spirit (150±8 vs 214±4 s, p<0.05), when compared to the control group. In addition, the ratio of the time spent in the open arms over the total time spent in both closed and open arms was significantly increased (ethanol 34±8 vs 6±2 s; sugarcane spirit 43±12 vs 6±2 s, p<0.05. In the hole board test, mice treated with ethanol or sugarcane spirit showed an increase in the number of head-dipping behaviors, when compared to the control condition (control group: 16±1; ethanol: 27±2; sugarcane spirit: 31±3, p<0.05). In addition, motor activity in the hole board test was also increased in both ethanol and sugarcane spirit groups, when compared to the control condition (control group: 21±2; ethanol: 34±2; sugarcane spirit: 40±4, p<0.05). The chemical composition analysis showed that the concentrations of ethanol, volatile acidity, esters, aldehydes, furfural, higher alcohols (n-propylic, isobutylic and isoamylics), methanol, copper and lead in the sugarcane spirit were below the upper limits allowed by the Ministry of Agriculture regulations for the production of spirits. In conclusion, here we report that chronic consumption of sugarcane spirit produces liver injury and anxiolytic-like effects in mice. The more pronounced liver injury caused by sugarcane spirit as suggested by the AST/ALT ratio might have been caused by other organic compounds present in the sugarcane spirit while the anxiolytic-like effect seems to be caused by both ethanol and other compounds present in sugarcane spirit. The mechanisms by which sugarcane spirit leads to more rapid liver injury than does ethanol should be examined in future investigations.